2011
DOI: 10.1055/s-0039-1698878
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Perception of Their Dentists

Abstract: Objectives:The aim of this study was to assess school children’s feelings and attitudes toward their dentist.Methods:A questionnaire designed to evaluate children’s attitudes and preferences toward dentists was completed by 583 children (289 females, 294 males) with age range 9–12 years attending public schools.Results:76% of the children who completed the questionnaire reported that they had been to the dentist before. Of the children who had visited the dentist, approximately 64% reported liking their visit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
80
4
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 11 publications
9
80
4
17
Order By: Relevance
“…Only 40% of children preferred them to wear facemask and eyeglasses. 25 In the present study, the mean heart rates during dental examination wearing visor and facemask and eyeshield were compared. The mean heart rate during dental examination wearing visor (81.55) was significantly lesser than during dental examination wearing facemask and eyeshield (84.49), which means that dental anxiety levels were lower when the dentist used visor during the dental examination than when the dentist used facemask.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 40% of children preferred them to wear facemask and eyeglasses. 25 In the present study, the mean heart rates during dental examination wearing visor and facemask and eyeshield were compared. The mean heart rate during dental examination wearing visor (81.55) was significantly lesser than during dental examination wearing facemask and eyeshield (84.49), which means that dental anxiety levels were lower when the dentist used visor during the dental examination than when the dentist used facemask.…”
Section: Discussionmentioning
confidence: 99%
“…A study identified that child patients have strong choices and preferences regarding the appearance of their dentists and recognizable fears associated with dental visits. Only 40% of children preferred them to wear facemask and eyeglasses …”
Section: Discussionmentioning
confidence: 99%
“…[262728] Meechan reported that the clinical impact of articaine's higher postinjection pain scores than lignocaine is negligible. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Survei menunjukkan bahwa antara 5-6% dari populasi dan 16% anak usia sekolah yang memiliki ketakutan terhadap dokter gigi. 3,4 Perawatan pada pasien anak berbeda dengan perawatan pasien dewasa.Hal ini pentingbagi dokter gigi untuk membangun hubungan yang bersahabat dengan pasien, terutama pasien anak, dalam rangka memerangi ketakutan pasien dan untuk memberikan perawatan yangefektifdanefisien.Adanya hubungan yang kuat pada kunjungan pertama anak membantu menciptakan suasananyaman sehingga mereka tidak merasa terancam. Anak sering membuat penilaian tentang dokter gigi mereka berdasarkan penampilan dokter gigi dan sering merekam serta menganalisis setiap kata, gerakan, dan isyarat dokter gigi mereka selama perawatan.…”
Section: Pendahuluanunclassified
“…Anak sering membuat penilaian tentang dokter gigi mereka berdasarkan penampilan dokter gigi dan sering merekam serta menganalisis setiap kata, gerakan, dan isyarat dokter gigi mereka selama perawatan. 1,4 Sebuahhubunganyangbersahabatdengandokter gigi membantu pasien dalam mengatasi rangsangan identifikasi khusus,seperti jarum suntik anastesi dan penglihatan, suara, dan sensasi dari handpiece dan bur yangtelah terbukti dapat memancing kecemasan. Miller menekankan perlunya mengurangi sebanyak mungkin kecemasan pasien dan ketakutan terhadap kedokteran gigi, karena ketakutan bermula di masa kecil, sehingga tepat memilih anak-anak sebagai target penelitian ini.…”
Section: Pendahuluanunclassified